VOLATILITAS PASAR UANG DAN PASAR MODAL SYARIAH: STRATEGI PENGUATAN EKOSISTEM INVESTASI DI INDONESIA - Maryam Batubara; Iin Prasetyo; Karmila Sinaga (Media Mahardhika, 2026)
The development of the Islamic finance sector in Indonesia, both in terms of the money market and the capital market, is inextricably linked to the Muslim community's need for a financial system that complies with the principles of freedom from usury, gharar, and maisir. These investments are, of course, carried out in accordance with Islamic principles as the economic jurisprudence of Caliph Umar bin Khatab recognised the role of capital in economic activities and its right to a share (percentage) of the proceeds from those activities. Through qualitative studies, this research concludes that the sharia money and capital markets in Indonesia play a strategic role in providing financial instruments that are in accordance with Islamic principles, as well as helping to strengthen the stability of the national financial system. To optimise the growth of the money market and sharia capital market, an integrated strategy is needed that combines solid regulations, increased Islamic financial literacy, the use of financial technology (fintech), and competitive product innovation.